The population structure of the lichen Lobaria pulmonaria in the middle boreal forests depends on the time-since-disturbance - Ignatenko, Roman V.; Tarasova, Viktoria N. (Folia Cryptogamica Estonica, 2017)
The population structure of the lichen Lobaria pulmonaria (L.) Hoffm. was analyzed in the Vodlozersky National Park (Karelia, Russia), for middle boreal forest stands having a time-since-disturbance spanning 80 to 450 years. To estimate the age of the last disturbance, a method of evaluation for the tree population structure was applied. The forest stand communities belonged to a successional series: middle-aged aspen – mixed aspen-spruce – pre-climax spruce – climax (old-growth) spruce forest. All thalli (1055) of L. pulmonaria from all substrate units (165, separately standing or lying trees and shrubs) were described within 7 sample plots of 1 ha. For each thallus, the area (cm2) and the functional-age group were determined. The number of Lobaria thalli per ha, number of substrate units, number of substrate types (living, standing dead and lying dead trees of different species) colonized by L. pulmonaria, as well as number of substrate types on which the lichen had completed its life cycle increased with time-since-disturbance.